Exploring links between Arctic amplification and mid‐latitude weather. Issue 5 (13th March 2013) - Screen, James A.; Simmonds, Ian
Abstract [1] This study examines observed changes (1979–2011) in atmospheric planetary‐wave amplitude over northern mid‐latitudes, which have been proposed as a possible mechanism linking Arctic amplification and mid‐latitude weather extremes. We use two distinct but equally‐valid definitions of planetary‐wave amplitude, termed meridional amplitude, a measure of north‐south meandering, and zonal amplitude, a measure of the intensity of atmospheric ridges and troughs at 45°N. Statistically significant changes in either metric are limited to few seasons, wavelengths, and longitudinal sectors. However in summer, we identify significant increases in meridional amplitude over Europe, but significant decreases in zonal amplitude hemispherically, and also individually over Europe and Asia. Therefore, we argue that possible connections between Arctic amplification and planetary waves, and implications of these, are sensitive to how waves are conceptualized. The contrasting meridional and zonal amplitude trends have different and complex possible implications for midlatitude weather, and we encourage further work to better understand these.